Proyek Inovasi Efektivitas Lilin Aromaterapi Lavender terhadap Kecemasan pada Pasien Pre-Operasi - Sukriyadi Adi; Musdalifa Muslimin; Muhammad Nur; Ismail Ismail; Hamzah Tasa (Celebes Health Journal, 2025)
Background: Preoperative anxiety is a common problem experienced by patients and can affect physical and psychological preparedness before surgery. This condition needs to be addressed through effective and safe approaches, including non-pharmacological interventions such as aromatherapy. Objective: This study aimed to assess the effectiveness of lavender aromatherapy candles in reducing anxiety in preoperative patients. Methods: The study used a quasi-experimental design with a pre-post test approach without control and involved 20 patients who met the inclusion criteria. Anxiety levels were measured before and after the intervention using a standard instrument suitable for assessing preoperative anxiety. Lavender aromatherapy candles were lit for the predetermined duration of the intervention to provide stable aroma exposure. Results: The results showed a significant decrease in the distribution of anxiety levels after the intervention. The moderate anxiety category decreased from 75% to 15%, and the severe anxiety category decreased from 10% to 0%. Conversely, the non-anxious category increased from 0% to 20%, and the mild anxiety category increased to 65%. Conclusions: These findings indicate that lavender aromatherapy candles provide a significant relaxation effect on preoperative anxiety. The study concluded that lavender aromatherapy candles were effective as a complementary intervention to reduce anxiety and could be applied in pre-surgical nursing services.